2019
DOI: 10.1186/s40644-019-0210-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of multislice spiral computed tomography (CT) combined with CT angiography for intra-abdominal undescended testis secondary seminomas

Abstract: Objective To discuss the diagnostic value of multislice spiral tomography (CT) combined with CT angiography (CTA) technology in intra-abdominal undescended testis secondary seminoma cases. Methods We retrospectively analyzed the CT and CTA imaging features of CT and CTA findings of nine patients with an intra-abdominal undescended testis secondary seminoma. Results The tumors in all nine patients were mainly solid, and the average CT value wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It has been shown that extrawall vascular invasion usually coexists with extraspinal nerve and lymphatic vessel infiltration and is a way of tumour spreading along the neurovascular tract [10]. Due to extrawall vascular invasion, tumour cells can spread throughout the portal system and eventually form distant metastasis [11].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that extrawall vascular invasion usually coexists with extraspinal nerve and lymphatic vessel infiltration and is a way of tumour spreading along the neurovascular tract [10]. Due to extrawall vascular invasion, tumour cells can spread throughout the portal system and eventually form distant metastasis [11].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography of testicular microlithiasis is characterized by scattered dot-like hyperechoic foci in the parenchyma of the testis. Therefore, when the hypoechoic mass outside the scrotum showed scattered dots in the parenchyma on ultrasound, it is highly indicated as IAT and EAT 17 19 ; 2. The average age of the children in this group was 2 years and 4 month, the abdomen was shallow, and the high-frequency probe had high resolution to the abdominal organs of infants and young children, which was conducive to the abdominal ultrasound examination of IAT and NVT; 3.…”
Section: Discussionmentioning
confidence: 99%
“…The etiologies and pathogenesis are unknown, part of patients with the absence of the greater omentum which are related to the congenital developmental abnormalities, the possible reason is that the greater omentum descends and wraps the intestine to form the smooth and dense cocoon membrane (13). Cryptorchidism mainly manifests as the absence of testicle in the affected scrotum (4,5,14), CT could accurately show the location of cryptorchidism in the abdominal cavity (15), and this disease may be related to the obstruction of testicular descent during embryonic development (14). In this case, he was admitted to the hospital due to unexplained intermittent abdominal pain, preoperative CT showed suspicious abdominal cocoon and right cryptorchidism.…”
Section: Discussionmentioning
confidence: 99%